Molecular Basis for Periodontal Ligament Adaptation to In Vivo Loading. (March 2019) - Zhang, X.; Yuan, X.; Xu, Q.; Arioka, M.; Van Brunt, L.A.; Shi, Y.; Brunski, J.; Helms, J.A.
A soft food diet leads to changes in the periodontal ligament (PDL). These changes, which have been recognized for more than a century, are ascribed to alterations in mechanical loading. While these adaptive responses have been well characterized, the molecular, cellular, and mechanical mechanisms underlying the changes have not. Here, we implicate Wnt signaling in the pathoetiology of PDL responses to underloading. We show that Wnt-responsive cells and their progeny in the PDL space exhibit a burst in proliferation in response to mastication. If an animal is fed a soft diet from the time of weaning, then this burst in Wnt-responsive cell proliferation is quelled; as a consequence, both the PDL and the surrounding alveolar bone undergo atrophy. Returning these animals to a hard food diet restores the Wnt signaling in PDL. These data provide, for the first time, a molecular mechanism underlying the adaptive response of the PDL to loading.